A new method to design post-mining landforms - Hancock, GR; Martín Duque, JF; Welivitiya, DP (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Designing and constructing post-mining landforms is a complex undertaking. Any structure requires integration with underlying materials and surrounding unmined or undisturbed landscape with consideration of the post-mining land use. A commonly used reconstruction design is to have linear hillslopes with drains or runoff diversion structures that are designed for the hillslope length, angle and climate. These landscapes are easy to construct and result in a surface which can be easily traversed by agricultural machinery while the benches often rely on drainage control structures to manage runoff and resultant erosion. At many sites these landscapes can be erosionally stable and successfully integrate with the surrounding landscape. An alternative to linear hillslopes is to employ a catchment focus for post-mining landscape shape. Few mines have committed to a catchment based reconstruction approach or that employing geomorphic design. The difficulty has been designing and constructing a post-mining catchment. Here, a new method for catchment design has employed a simple strategy of that of an uplifted catchment being allowed to evolve using a computer based landscape evolution model until the volume matches that of a proposed design. The landscape evolution model employs site and material specific hydrology and erosion parameters which produce a landscape which potentially represents that geomorphological evolution. The results demonstrate that a computer generated landscape produces sediment output within that of target erosion rates with low gully depths. The computer model generated catchment also has a more natural appearance. A key finding is that landscapes with a series of smaller catchments and a more complex drainage network produce less sediment output.
Keywords: Landscape evolution model